KEPEMIMPINAN WANITA DALAM PERSPEKTIF SYARI’AH - Zuman Malaka (Jurnal Keislaman, 2021)
Leadership in Islam is also called the caliph which is the executor of Allah's authority in realizing his various commands in the lives of fellow human beings. And the urgent problem at this time is women's leadership, many layers of society and Muslims themselves are debating about the existence of women's leadership, both of which have the same opinion regarding the legal position of women as leaders; First, the concept/interpretation that is forbidden and the second is that which allows it. Both are based on the verses of the Qur'an and the hadith of the prophet Muhammad SAW. Actually, this problem is not new, but it has been going on for centuries, and in Indonesia this is also very common. For these reasons, it is necessary to interpret the Qur'an and Hadith regarding women's leadership in a sharia perspective in order to know and analyze women's leadership.